2022
DOI: 10.1002/vro2.36
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and attitudes towards companion animal brain banking in pet owners: A UK pilot study

Abstract: Background: Detailed analysis of archived brain tissue is fundamental to advancing the understanding of neurological disease. The development of the UK Brain Bank Network (UBBN) has provided an invaluable resource to facilitate such research in the human medical field. Similar resources are needed in veterinary medicine. However, collection and archiving of companion animal brain tissue is a potentially sensitive area for pet owners and veterinary professionals. Methods: Using an online survey, we aimed to stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…A 2022 study conducted by Cardy and colleagues used an online survey to review the perceptions of pet owners on companion animal brain banking. The survey included mainly multiple-choice questions and Likert Scales with one response-based question giving participants a chance to explain their choice (Cardy et al, 2022). 66% of participants felt they would be likely or highly likely to donate the brain tissue of their pet, whereas 14% indicated being unlikely or highly unlikely to do so (Cardy et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A 2022 study conducted by Cardy and colleagues used an online survey to review the perceptions of pet owners on companion animal brain banking. The survey included mainly multiple-choice questions and Likert Scales with one response-based question giving participants a chance to explain their choice (Cardy et al, 2022). 66% of participants felt they would be likely or highly likely to donate the brain tissue of their pet, whereas 14% indicated being unlikely or highly unlikely to do so (Cardy et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The survey included mainly multiple-choice questions and Likert Scales with one response-based question giving participants a chance to explain their choice (Cardy et al, 2022). 66% of participants felt they would be likely or highly likely to donate the brain tissue of their pet, whereas 14% indicated being unlikely or highly unlikely to do so (Cardy et al, 2022). 71% of those who supported pet brain tissue donation believed it would contribute significantly to research (Cardy et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This survey represents one of only a few published assessments of owners’ perspectives on veterinary biobanking. Cardy et al recently evaluated perspectives on veterinary biobanking, predominately in pet owners residing in the UK, and specifically in the context of animal brain banking ( 2 ). Our results support those previously reported that most people are not inherently familiar with veterinary biobanking initiatives but after a cursory introduction, are highly receptive and supportive of the idea of allowing their pet to contribute.…”
Section: Discussionmentioning
confidence: 99%